FENOMENA HABIB TERHADAP PUBLIK DALAM TEOLOGI DAN SOSIOLOGI - Kurdi, Sulaiman; Alamudi, Ichwan Ahnaz; Syafiq, Muhammad (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
Abstract This research is motivated by the fact that there are still many polemics in society that do not understand the term habib and how others should see the term itself. Most people know this term only from following along and understanding clouds that are not scientific. The occurrence of this polemic is due to the controversy of the habib phenomenon, so that there are groupings of people who are pro and contra to this term. Researchers want to know how the habib phenomenon becomes an interesting matter to be traced further in its development, whether it is related to religious and social contexts. This research is a qualitative research of the literature study type. This research shows that the phenomenon of the habib has received various reactions in society even to the point of a challenge to be able to prove the claim for the habaib who say the habaib are descendants of the Prophet. Furthermore, the Habib title needs a clear understanding of meaning for the community so that people follow Habib no more than a teacher who must be respected and loved. The term habib must be understood not as a privilege, but as a form of responsibility as someone who has genealogy from the Messenger of Allah Sallallahu Alaihi Wasallam. Keyword: Phenomenon, Habib, Theology, Sociology.